Proceso tecnológico para la elaboración de una mermelada agridulce combinada de carambola (averrhoa carambola) y mango (Tommy Atkins), en el cantón Santo Domingo 2013. Quevedo - Uchuari Palma, Rosa Gabriela (2013)
The purpose of this research is to use the fruit (Carambola and Mango) and fix the rate of loss in postharvest fruit presenting today, besides the little information on the nutritional benefits that have these two fruits. Harnessing carambola be seen as a good alternative agriculture that so far has not given any industrial purpose, and as to a better way to handle serious conservation because this fruit is in season estimated between the months of October to December. Whereas the preparation of fruit preserves provides product stability, the development of fruit and mango jam was proposed as an alternative to the contribution to the technology industry in Ecuador…..